Epigenetic "Drivers" of Cancer. Issue 15 (23rd July 2021) - Butera, Alessio; Melino, Gerry; Amelio, Ivano
Graphical abstract: Highlights: Alterations of the cellular epigenome can "drive" cancer pathogenesis. Gene-environment interactions can dictate pro-tumorigenic epigenetic programs. Epigenetic deregulations can promote cancer also directly affecting genomic integrity Epigenetic signature should be considered as biomarkers of disease outcome Abstract: Genetics is at the basis of cancer initiation and evolution, but emerging evidence indicates that mutations are not sufficient to produce cancer, indicating a role for epigenetic contributions to the different stages of tumorigenesis. While the genetic tracks of cancer have been widely investigated, the epigenetic "drivers" remain a vague definition. Gene-environment interactions can produce gene-regulatory programs that dictate pathogenesis; this implies a reciprocal relationship where environmental factors contribute to genetic mechanisms of tumorigenesis (i.e. mutagenesis) and genetic factors influence the cellular response to extrinsic stress. In this review article, we attempt to summarise the most remarkable findings demonstrating a contribution of epigenetic factors as proper "drivers" of tumorigenesis. We also try to pose attention on the relevance of epigenetic mechanisms as downstream consequences of genes versus environment interaction.